Q: Solve for X: Step 2

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

How do you get x by itself? Subtract 2 from both sides

Yes you can answer it! -- Step 1. 2x(6)=4 Step 2. 2x=4/6 Step 3. 2x=0.6 (repeating) Step 4. x=0.6 (repeating)/ 2 Step 5. x=0.3 (repeating)

Well, that's one method to solve the quadratic equation. Here is an example (using the symbol "^" for power): solve x^2 - 5x + 6 = 0 Step 1: Convert the equation to a form in which the right side is equal to zero. (Already done in this example.) Step 2: Factor the left side. In this case, (x - 3) (x - 2) = 0 Step 3: Use the fact that if a product is zero, at least one of its factors must be zero. This lets you convert the equation to two equations; x - 3 = 0 OR x - 2 = 0 Step 4: Solve each of the two equations.

Check your work by substituting the answer, 5, into the equation for x. Does 2 + 5 = 7? Yes, so the correct answer is x = 5.

2/12 = m/18 ie 12 x m = 2 x 18 ...

Related questions

How do you get x by itself? Subtract 2 from both sides

1111111111111111111111111111111111111111111111111

Yes you can answer it! -- Step 1. 2x(6)=4 Step 2. 2x=4/6 Step 3. 2x=0.6 (repeating) Step 4. x=0.6 (repeating)/ 2 Step 5. x=0.3 (repeating)

algebraic equations that require 2 or more steps to solve. ex: 3(x - 2) = x + 8

Well, that's one method to solve the quadratic equation. Here is an example (using the symbol "^" for power): solve x^2 - 5x + 6 = 0 Step 1: Convert the equation to a form in which the right side is equal to zero. (Already done in this example.) Step 2: Factor the left side. In this case, (x - 3) (x - 2) = 0 Step 3: Use the fact that if a product is zero, at least one of its factors must be zero. This lets you convert the equation to two equations; x - 3 = 0 OR x - 2 = 0 Step 4: Solve each of the two equations.

-2x = -4x + 24 -2x + 4x = 24 2x = 24 x = 24/2 x = 12

Check your work by substituting the answer, 5, into the equation for x. Does 2 + 5 = 7? Yes, so the correct answer is x = 5.

Step 1. Let x be the number of 30 cents stamps. Step 2. Let x-2 be the number of 20 cents stamps. Step 3. Let 30x be the cost of buying x number of 30 cents stamps Step 4. Let 20(x-2) be the cost of buying x-2 number of 20 cents stamps. Step 5. 30x+20(x-2)=360 cents is the total cost of buying stamps. Step 6. The following steps will solve the equation in Step 5:

It all depends what x is equal to. But let's say you know what x is. 1. Multiply x by 2 2. Add 4 to step one's result 3. You've got your answer!

The equation to solve is given by. |-2 x + 2| -3 = -3 Add 3 to both sides of the equation and simplify. |-2 x + 2| = 0 |-2 x + 2| is equal to 0 if -2 x + 2 = 0. Solve for x to obtain. So, x = 1

2/12 = m/18 ie 12 x m = 2 x 18 ...

That depends a great deal on the equation that x + 2 should be a part of. In order to solve for x, x + 2 needs to equal something. If x + 2 = 0, x = -2 If x + 2 = 4, x = 2